Reasonable design of thick electrodes in lithium-ion batteries - Sim, Yoon Bo; Park, Bo Keun; Kim, Ki Jae (Frontiers in Batteries and Electrochemistry, 2023)
To achieve a high energy density for Li-ion batteries (LIBs) in a limited space, thick electrodes play an important role by minimizing passive component at the unit cell level and allowing higher active material loading within the same volume. Currently, the capacity of active materials is close to the theoretical capacity; therefore, thick electrodes provide the clearest solution for the development of high-energy-density batteries. However, further research is needed to resolve the electrochemical and mechanical instabilities inside the electrode owing to its increased thickness. This review summarizes the various methods and recent research aimed at fabricating electrodes with low-torsion and uniform pore structure for fast ion transport, based on an in-depth consideration of the challenges encountered in thick electrodes. In addition, future developments and research directions necessary to apply these methods to the industry are presented. This review will be a valuable milestone for manufacturing robust thick electrodes with high performance and for realizing ultrahigh-capacity/density batteries in the future.